Resilience-focused interventions for post- stroke depression: A systematic review - Liberti Hariyani; I Made Kariasa; Riri Maria (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Stroke is one of the leading causes of long-term disability and morbidity worldwide. Post-stroke depression (PSD) is a common psychological complication that negatively affects recovery, functional outcomes, and quality of life. Psychological resilience is considered a key factor in helping patients adapt to post-stroke challenges; however, evidence regarding effective interventions to strengthen resilience in patients with PSD remains limited. Purpose: To evaluate the effectiveness of interventions that potentially enhance resilience-related components in patients with post-stroke depression and to provide evidence-based recommendations for nursing and clinical practice. Method: A systematic review was conducted in accordance with the PRISMA 2020 guidelines. Literature searches were performed across five databases such as PubMed, Scopus, ScienceDirect, ProQuest, and Wiley using the keywords post-stroke depression, resilience, and intervention. Randomized controlled trials published in English that involved PSD patients and reported psychological outcomes related to resilience were included. Of 9,241 identified records, nine studies involving 779 participants met the inclusion criteria and were analyzed using narrative synthesis. Results: Psychological interventions, including Acceptance and Commitment Therapy (ACT) and Mindfulness-Based Interventions (MBI), showed significant improvements in psychological flexibility (25–35%), mindfulness (20–32%), and coping ability (15–25%), alongside a significant reduction in depressive symptoms (p < 0.001). Physical-based interventions such as Tai Chi and Yijinjing Qigong were associated with improved emotional regulation and reductions in depressive symptoms of up to 45%. Technology-assisted approaches, particularly Virtual Reality interventions, reduced depressive symptoms by up to 22%. Pharmacological treatments demonstrated faster mood improvement but showed limited effects on strengthening psychological resilience. Conclusion: ACT, MBI, and structured physical exercise appear to be the most effective interventions for enhancing resilience-related components and alleviating depressive symptoms in patients with post-stroke depression. Future studies are recommended to directly measure resilience outcomes and examine the long-term sustainability of these interventions.